Factors associated with work volition among Chinese undergraduates - Hai, Lu; Bao, Xiaohong; Li, Wenyu (Frontiers in Psychology, 2022)
Based on the psychology of working theory, this study tested the relationships among work volition and the predictors of economic constraints, minzu (ethnic identity), hukou, and Zhongyong thinking, and how hukou and Zhongyong thinking moderate the relationship between economic constraints and work volition with a sample of 2995 undergraduates in China. The results showed that work volition was negatively associated with economic constraints but positively related to Zhongyong thinking. The results further revealed that hukou and Zhongyong thinking were significant moderators in the link between economic constraints and work volition, while weaker negative associations were found with undergraduates who came from rural areas and had lower levels of Zhongyong thinking. Implications for research and practice are discussed.